Development of Vocaroom Educational Game to Improve English Vocabulary Comprehension for Elementary School Students - Putri Nur Anafi; Petra Kristi Mulyani (Program Studi PGSD, Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2025)
This study aims to develop, evaluate the feasibility of, and analyze the potential effectiveness of the vocaroom educational game as a Canva-based instructional tool to improve English vocabulary comprehension for fourth-grade students. Utilizing the Research and Development method with the ADDIE model, the study involved 28 students at SDN Patemon 01 Semarang through a one-group pre-test-post-test design. The unique contribution of this medium lies in its integration of contextual spatial visualization and bilingual audio, which transforms conventional static digital flashcards into an explorative room-mapping experience. Through the Map Challenge and Room Conditions, students are encouraged to understand vocabulary within a concrete environmental context rather than through isolated rote memorization. Expert validation results indicate that the medium is highly feasible for implementation, with scores of 93 percent from material experts and 95 percent from media experts, confirming its alignment with the Kurikulum Merdeka. Statistical analysis using the Wilcoxon Signed Ranks Test yielded an Asymp Sig 2-tailed value of 0.000, suggesting a significant improvement in student learning achievement from an average of 65.64 to 94.71. An N-Gain score of 0.8286 further suggests high effectiveness within this specific research context. Although these results are promising, the study acknowledges the limitations of a one-group design; therefore, further quasi-experimental research is recommended to strengthen the generalizability of the findings. Overall, the vocaroom educational game serves as a credible instrument to improve English vocabulary comprehension through an interactive spatial-mapping approach.